Implementasi Supervisi Akademik Dalam Meningkatkan Kinerja Guru Di Mts Al-Ma'arij Kecamatan Cicantayan Kabupaten Sukabumi - Ujang Natadireja; Siti Qomariyah; Rubi Babullah; Rima Ervina; Siti Nurafifah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to examine the implementation of academic supervision in improving teacher performance at MTs Al-Ma'arij, Cicantayan District, Sukabumi Regency. Academic supervision is an essential effort to enhance the quality of education through the guidance and supervision of teacher performance. The research method used is descriptive with a qualitative approach. Data were obtained through interviews, observations, and documentation. The results of the study indicate that the academic supervision implemented at MTs Al-Ma'arij includes supervision planning, supervision execution, and supervision evaluation. The implementation of academic supervision has proven effective in improving teacher performance, marked by increased pedagogical competence, professionalism, and work motivation among teachers. The obstacles encountered in the implementation of academic supervision include limited time, facilities, and infrastructure. To overcome these obstacles, it is recommended to enhance supporting facilities and provide continuous training for supervisors and teachers.